Utility of mitochondrial‐encoded cytochrome c oxidase I gene for phylogenetic analysis and species identification of the planktonic diatom genus Skeletonema. Issue 3 (19th April 2017) - Yamada, Machiko; Otsubo, Mayuko; Tsutsumi, Yuki; Mizota, Chiaki; Nakamura, Yuka; Takahashi, Kazuya; Iwataki, Mitsunori
SUMMARY: Small subunit (SSU) and large subunit (LSU) rDNA sequences have been commonly used to delineate the taxonomy and biogeography of the planktonic diatom genus Skeletonema, but the genes occur as multiple copies and are therefore not suitable for barcoding purposes. Here, we analyzed phylogenetic relationships of Skeletonema using the mitochondrial‐encoded cytochrome c oxidase I gene ( cox 1), as well as partial LSU rDNA (D1–D3) and SSU rDNA, to identify the factors that define species and to evaluate the utility of these three markers for this taxon. Twelve Skeletonema species were divided into six clades, I–VI, each of which comprised the same species by the three markers: clades I ( S. japonicum, S. grethae, S. pseudocostatum, and S. tropicum ), II ( S. menzelii ), III ( S. dohrnii and S. marinoi ), IV ( S. costatum, S. potamos, and S. subsalsum ), V ( S. grevillei ), and VI ( S. ardens ). However, the branching order among these clades was incongruent among the markers. In clade III, six S. marinoi strains had identical cox 1 sequences. These S. marinoi strains branched along with S. dohrnii, except for strains from the Gulf of Naples, with high support in cox 1. Species delimitation between S. dohrnii and S. marinoi was therefore not supported. In clade IV, S. costatum and S. subsalsum were robustly clustered, with S. potamos as a sister clade in the cox 1 tree, not in the LSU and SSU trees. In clade II, cox 1 also confirmed that S. menzelii includes three subclades potentially distinguishable from each other by morphological features. Cox 1 proved to be the most useful marker for the identification of Skeletonema species because it gave a tree with highly supported clades, has sufficient variation within and among species, encodes a protein in a single copy, and requires relatively few primers.